ASPAL: POTENSI WISATA HERITAGE DI PULAU BUTON (STUDI KASUS DI DESA WINNING) - Sari, Dhanik Puspita (Jurnal Hospitality dan Pariwisata, 2023)
Buton Island in Southeast Sulawesi is famous for its asphalt content, one of the asphalt mining sites that is rich in heritage tourism potential is in Winning Village, Buton Regency. This research aims to provide an overview of the activities that are still actively carried out in the mining area and also what heritage tourism potential exists in the asphalt mining area in Winning Village. The method used is descriptive qualitative. Primary data was collected through field observations and interviews while secondary data came from literature review and documentation. The mining activities currently still being carried out are asphalt mining activities, which are then processed into several stages to become smaller asphalt rocks ready to be sent through the Banabungi port in the Pasarwajo area. While the potential for heritage tourism in this area is in the form of a complex area of former offices, hospitals, and asphalt workers' settlements with the condition of buildings that are still standing and there has not been any change or renovation which has high historical value. The potential for heritage tourism attractions is very high, existing amenity is still very limited and accessibility is quite good.